Manajemen Kurikulum Kulliyatul Mu’allimin Al-Islamiyyah di Pondok Modern Darussalam Gontor - Syarifah Syarifah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
Most People assume Madrasah or Pesantren as second-classeducational institutions compared with state education institutions, thelack of professionalism in school management becomes a reason for animprovement in it. Whereas a Pesantren is the oldest educational system inIndonesia, whose existence has been proven by history and continues untilknow. and it is the pioneer of education system that become the foundationof education ideology in Indonesia. Therefore, it is need to hold in-depthstudy on the management of the curriculum in Madrasah or pesantren.This paper aims to review the curriculum management in Pondok ModernDarussalam Gontor. Because this Pesantren is an educational institutionthat is very well-known internasiaonally. This study found that PondokModern Gontor implement integrative, comprehensive and independenteducation system. Integrative means the integration of intra, extra and cocurricularactivities. So as to consistently integrate Three education center.Comprehensive means cover all aspect and complete, sharpening allpotential (intellectuality, spirituality, mentality, as well as physicaly). andindependent because the curriculum is the result of its own formulation,composed by education personnel who are experts in their fields, and thewhole composers is a teachers in Pondok Modern Darussalam Gontor. Thesystem of Gontor has become a phenomenon in the developomental ofeducation in Indonesia. this educational system could be compared withMuhammadiyah and Taman Siswa.